Spatial and Temporal Growth Variation of Pinus heldreichii Christ. Growing along a Latitudinal Gradient in Kosovo and Albania - Faruk Bojaxhi; Elvin Toromani (South-East European Forestry, 2017)
Background and Purpose: Trees growing at high elevations are particularly sensitive to climate variability. In this study, tree-ring chronologies of Pinus heldreichii Christ. have been developed to examine their dynamism along a 350 km latitudinal gradient. Materials and Methods: Sampling was conducted in 6 high elevation sites along a latitudinal gradient from Kosovo and Albania. Two opposite cores from 148 healthy and dominant P. heldreichii trees were taken using an increment borer. The cores were mounted and sanded, and after a rigorous cross-dating, the ring widths were measured to a resolution of 0.01 mm using the LINTAB 6 measuring device. The ARSTAN program was used for tree-ring series detrending and site chronologies’ development. The relationship between radial growth and climate, as well as between temporal patterns of P. heldreichii growth were investigated using simple correlation analysis and principal component analysis (PCA) over the common period 1951-2013. Results: Radial growth variability of Bosnian pine increased with latitude and elevation. Significant correlations among our chronologies and others from neighbouring countries indicated that our chronologies possess a good regional climatic signal. P. heldreichii growth at all sampling sites was significantly influenced by seasonal and mean annual temperatures, as well as by the July drought. Thus, temperature was the main driving force of species growth, showing a larger control at spatial scale than precipitation. The difference in species growth patterns along the latitudinal gradient is implicated by the common action of climatic and non-climatic factors (age and human activity). With continued warming and precipitation decrease during the second half of the 20th century, P. heldreichii growth from these high elevation sites resulted in being more sensitive to drought. This climatic signal is assumed to be stronger in the future due to climate change. Conclusions: P. heldreichii chronologies developed in our study possess a good local and regional climatic signal. Temperature was the main driving force of P. heldreichii growing in these high elevations sites. The reduction of P. heldreichii growth during the second half of the 20th century due to temperature rise and rainfall decrease imposes the necessity to continue investigations​ on potential impacts of climate warming on species growing near the tree-line.